Metode Eksplorasi Berbasis Audio Dalam Meningkatkan Motivasi Belajar Siswa - Agus Zainudin; Elga Yanuardianto; Firdaus Roni Efendi (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines the implementation of the exploration method in dance arts learning, focusing on its application, obstacles, and evaluation for broader adoption across grade levels. Using a qualitative phenomenological design, the research involved purposively selected participants who possessed in-depth knowledge of the learning process. Data were collected through classroom observations, in-depth interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques. The findings show that the exploration method effectively increased students’ enthusiasm, motivation, and active participation in dance arts learning. Students were more engaged in expressing movement ideas and responding creatively to learning activities. However, the implementation faced obstacles, particularly classroom conditions that allowed distractions from other students, which sometimes reduced learners’ concentration during activities. Limitations in classroom management and learning space also influenced the effectiveness of the method. Overall, the exploration method demonstrates positive potential for supporting student-centered learning in dance arts. To optimize its implementation, practical strategies are required, including improved classroom management and supportive learning environments. With proper adjustments, this method can be considered for wider application at various educational levels.